2006
DOI: 10.1007/s11517-005-0002-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of manual sleep staging with automated neural network-based analysis in clinical practice

Abstract: We have compared sleep staging by an automated neural network (ANN) system, BioSleep (Oxford BioSignals) and a human scorer using the Rechtschaffen and Kales scoring system. Sleep study recordings from 114 patients with suspected obstructed sleep apnoea syndrome (OSA) were analysed by ANN and by a blinded human scorer. We also examined human scorer reliability by calculating the agreement between the index scorer and a second independent blinded scorer for 28 of the 114 studies. For each study, we built contin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
30
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 13 publications
2
30
0
1
Order By: Relevance
“…are analyzed by the Physician. 11 50 Manual is accurate scoring method Nigro et al 12 96 Manual is accurate scoring method OZ turko et al 13 30 Manual is accurate scoring method J.caffarel et al 14 114 Manual is accurate scoring method B. Barreiro et al 15 28 Manual is accurate scoring method Carrasco O et al 16 36 Manual is accurate scoring method N Schaltenbrand et al 17 60 Manual is accurate scoring method St.Kubicki et al 18 34 Manual is accurate scoring method A Malhotra et al 19 70 Auto with manual editing Stephen D et al 20 31 Auto with manual editing Present study 100 Manual is accurate scoring method …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…are analyzed by the Physician. 11 50 Manual is accurate scoring method Nigro et al 12 96 Manual is accurate scoring method OZ turko et al 13 30 Manual is accurate scoring method J.caffarel et al 14 114 Manual is accurate scoring method B. Barreiro et al 15 28 Manual is accurate scoring method Carrasco O et al 16 36 Manual is accurate scoring method N Schaltenbrand et al 17 60 Manual is accurate scoring method St.Kubicki et al 18 34 Manual is accurate scoring method A Malhotra et al 19 70 Auto with manual editing Stephen D et al 20 31 Auto with manual editing Present study 100 Manual is accurate scoring method …”
Section: Discussionmentioning
confidence: 99%
“…6 The abnormal craniofacial characteristics include retrognathia, micrognathia, inferior positioning of hyoid bone, long and large soft palate, large tongue etc. 7,8 Patients with OSA have increased adipose tissue deposition lateral to pharynx. 9 OSA is a heterogenous disease process.…”
mentioning
confidence: 99%
“…They reported that patients who lay on mattresses with normal stiffness experience less pain in their back than the ones with high stiffness mattress. Drinnan et al [17] characterized the various rest postures and separated them by a difference in parameters determined with electroencephalogram (EEG), electrooculogram (EOG), and electromyogram (EMG) amplitudes. Hansson et al [6] investigated the root mean square (RMS) of EMG data to present the distribution of various activity levels of neck muscles while at rest.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the cost and complexity of measuring and processing multiple signal channels, manual sleep staging is also tedious, time consuming, and errorprone. In response to these challenges, many automatic sleep staging methods using statistical learning or artificial intelligence techniques have been developed (Park et al, 2000, Agarwal and Gotman, 2001, Caffarel et al, 2006, Porée et al, 2006, Tagluk et al, 2010and Pan et al, 2012. The complexity of the sleep staging problems can be furthered alleviated by extracting features from fewer signal channels (Agarwal et al, 2005, Berthomier et al, 2007, Virkkala et al, 2007a, Virkkala et al, 2007b, Malinowska et al, 2009, Güneşa et al, 2010, Levendowski et al, 2012and Stepnowsky et al, 2013.…”
Section: Introductionmentioning
confidence: 99%